2020
DOI: 10.9734/irjpac/2020/v21i2430343
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Index of Selected Indian Rice Varieties

Abstract: Aims: For prevention and management of type II diabetes among rice eating population, consumption of rice with lower Glycemic Index (GI) is highly desirable as low GI food decreases plasma glucose levels and plasma insulin demand. As there is paucity of information on the GIs of commonly consumed rice varieties in India, the aim of this study was to determine GI of selected five rice varieties, and to find relationship of GI with their cooking and eating quality traits. Study Design, Place and Duration: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…A similar positive association was also reported by Azam et al . (2020) where they concluded that lower WU upon cooking is a good predictor for low GI rice. The strong correlation may be explained as WU mainly involves hydrothermal processing of rice which can be held responsible for altering the effects of starch and non‐starch components on starch digestion (Khatun et al ., 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar positive association was also reported by Azam et al . (2020) where they concluded that lower WU upon cooking is a good predictor for low GI rice. The strong correlation may be explained as WU mainly involves hydrothermal processing of rice which can be held responsible for altering the effects of starch and non‐starch components on starch digestion (Khatun et al ., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Rice typically falls into the category of foods with GI ranging from 55–69 to >70. Foods low in GI (<55) slow down the pace at which starch is hydrolyzed, thus helping in decreasing levels of plasma glucose, insulin response and plasma insulin demand (Azam et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GI was calculated by using IAUC. (Azam et al, 2020). Variation caused in RS due to the proportion of amylose to amylopectin in grains may decrease total GI in foods after cooking.…”
Section: Discussionmentioning
confidence: 99%